Escaping from low-wage employment: The role of co-worker networks - Anna Baranowska-Rataj; Zoltán Elekes; Rikard Eriksson (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
Low-wage jobs are often regarded as dead-ends in the labour market careers of young people. Previous research focused on disentangling to what degree the association between a low-wage job at the start of working life and limited chances of transitioning to better-paid employment is causal or spurious. Less attention has been paid to the channels that may facilitate the upward wage mobility of low-wage workers. We focus on such mechanisms, and we scrutinize the impact of social ties to higher-educated co-workers. Due to knowledge spillovers, job referrals, as well as firm-level productivity gains, having higher-educated co-workers may improve an individual's chances of transitioning to a better-paid job. We use linked employer-employee data from longitudinal Swedish registers and panel data models that incorporate measures of low-wage workers' social ties to higher-educated co-workers. Our results confirm that having social ties to higher-educated co-workers increases individual chances of transitioning to better-paid employment.
Keywords: C23; D85; J24; J31; 330; co-worker networks; employer-employee data; low-wage; wage mobility